EVALUATION OF ELF PUBLIC TRANSPORTATION SERVICES IN CIREBON REGENCY: ABILITY TO PAY, SATISFACTION, AND CONVENIENCE BEFORE AND DURING THE PANDEMIC - Andis Destrian Irianto (RADJA PUBLIKA, 2025)
The COVID-19 pandemic has disrupted various sectors in Cirebon Regency, including the transportation system, especially elf-type city transportation services. This study aims to analyze the ability to pay, level of satisfaction, and ease of public access to elf transportation services in Cirebon Regency. Data collection was conducted through an online questionnaire survey with 100 respondents, determined using the Slovin method with a margin of error of 10%. The results showed that the average tariff set by elf drivers was Rp3.038,46, while the majority of respondents were able to pay up to Rp 4.000,00. Before the pandemic, ease of access was considered quite good, but decreased during the pandemic due to operational restrictions and fleet reduction. User satisfaction levels have been stable, with the majority of respondents rating the service as adequate. These findings suggest that despite the pandemic, public acceptance of elf services remains high. Therefore, policies that support the sustainability of public transportation are needed, such as improving comfort, operational efficiency, and adjusting tariffs according to people's purchasing power. This has been proven in the field, with these improvements making it easier for people to access mobility and also having an impact on the regional economy.